Speaking Challenges Among English Club Members at One Islamic Boarding School in South Sumatera - Lenny Marzulina; Muhamad Holandyah; Dian Erlina; Herizal Herizal; Hikmah Zalifah Putri; Lia Hidayati (The Journal of English Literacy Education: The Teaching and Learning of English as A Foreign Language, 2024)
This present study aimed at investigating speaking challenges encountered by students participating in an English Club at Daarul Abroor Islamic boarding school, Banyuasin, South Sumatera, Indonesia. This study employed qualitative research methods, utilizing a case study approach. Data were collected through observation, and  interview. The participants included six students who had joined the English club. The data were analyzed using thematic analysis. The results indicated that the challenges faced by students in speaking English within the club included a lack of vocabulary, reliance on their mother tongue, insufficient self-confidence, and low motivation. Recognizing the challenges students face in their speaking practice at the English Club is important for developing effective solutions to create a more supportive environment.